Understanding colloidal behavior in açaí (Euterpe oleraceae)-based nanoemulsions - Ferreira,Mikaela; Rocha,Leandro Machado; Cruz,Rodrigo; Machado,Francisco Paiva; Ronconi,Celia Machado; Fernandes,Caio (PeerJ Organic Chemistry, 2025)
Background In recent years there has been growing interest in novel, eco-friendly, natural product-based colloids, including nutraceuticals and cosmetics. Despite the Amazon region’s globally recognized biodiversity, efforts to sustainably use natural products for viable applications remain at the forefront of innovation. The superfruit Euterpe oleracea Mart, commonly known as açaí, is recognized by its high level of phenolic compounds and valuable oil. However, to the best of our knowledge, studies on its colloidal chemistry and the combination of its oil with phenolic-rich extract are scarce. Therefore, the aim of this study was to evaluate the generation of nanoemulsions containing açaí oil and phytoglycerol extract through a low-energy method, investigating the influence of surfactant’s nature and ratio on the droplet formation and stabilization, enhancing the potential for sustainable product development. Methods Total phenolics in the açaí-based phytoglycerol extract obtained from Heide Extratos Vegetais® were quantified using the Folin-Ciocalteau/Basf method. The nanoemulsions containing açaí oil and phytoglycerol extract were evaluated using individual or blended non-ionic surfactants with hydrophilic-lipophilic balance (HLB) values ranging from 9 to 15. The nanoemulsions consisted of 90% (w/w) aqueous phase (5% phytoglycerol extract in deionized water) and 10% (w/w) oily phase (varying ratios of açaí oil to surfactants, 7:3 to 9:1). The formulations were monitored for color, appearance, and p signs of instability. Additional systems were then prepared using twice the amount of oily phase, followed by a 1:1 dilution in the aqueous phase to achieve the same concentrations as previously reported. The optimal systems were subjected to dynamic light scattering analysis at room temperature (25 °C) and after a linear temperature ramp. Results The spectrophotometric characterization revealed that the phytoglycerol extract contains 2.8 ± 0.4 mg/mL of gallic acid equivalents. Various instability phenomena were observed at most surfactant-to-oil ratio (SOR) and with different surfactants. However, suitable açaí-based nanoemulsions were achieved using polysorbate 85 (HLB 11) and a combination of polysorbate 80/sorbitan monooleate (HLB 13) at an SOR of 9:1. The nanoemulsions with this pair of surfactants exhibited smaller droplet sizes (ca 200 nm) and showed no statistically significant difference in size during storage. The slope of size versus temperature also indicated that the nanoemulsion with polysorbate 80/sorbitan monooleate (HLB 13) at an SOR of 9:1 was more stable that the system prepared solely with polysorbate 85 (HLB 11).
Keywords: Euterpe oleracea; Dynamic light scattering; Extracts; Nanodroplets